1986
DOI: 10.1037/0021-843x.95.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among gifted women: A prospective study.

Abstract: The longitudinal data from the Terman Genetic Studies of Genius were used to predict suicide in 40 women: 8 suicides, 15 women who were matched with the suicides on age of death, and 17 subjects who were still living in 1964. Seven variables from the subjects 1 files were assessed as possible predictors of suicide: subject's physical health, early loss of the father, stress in the family of origin, problems with alcohol, and three indices of mental health. A discriminant function analysis was able to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The Terman data have been discussed by Shneidman (1981), who found that certain indicators of perturbation present in the files of the Terman men Ioumal for the Education of the Gifted who committed suicide made it possible to discriminate them from others who had died of natural causes and from those still living. Tomlinson-Keasey, Warren, and Elliott (1986) made similar findings in a study of Terman women. The indicators, or signatures, were drug or alcohol abuse, prior suicide threats or attempts, noticeable instability, depression, anxiety, ongoing stress either in the childhood or adult family, problems in parent-child relationships from early on, and homosexuality.…”
supporting
confidence: 85%
“…The Terman data have been discussed by Shneidman (1981), who found that certain indicators of perturbation present in the files of the Terman men Ioumal for the Education of the Gifted who committed suicide made it possible to discriminate them from others who had died of natural causes and from those still living. Tomlinson-Keasey, Warren, and Elliott (1986) made similar findings in a study of Terman women. The indicators, or signatures, were drug or alcohol abuse, prior suicide threats or attempts, noticeable instability, depression, anxiety, ongoing stress either in the childhood or adult family, problems in parent-child relationships from early on, and homosexuality.…”
supporting
confidence: 85%
“…Lester found that participants whose mothers experienced longer pregnancies and who themselves experienced an early loss of another by death were more likely to have committed suicide at a younger age. Other studies (Tomlinson-Keasey & Warren, 1987;Tomlinson-Keasey, Warren, & Elliott, 1986) utilized longitudinal data from Terman's sample, but focused entirely on female participants. In these two articles, discriminant function analyses were performed utilizing seven risk factors as predictors of membership in three groups, those who committed suicide, living controls, and deceased controls.…”
Section: Review Of the Research Literature On Suicide Among Gifted Stmentioning
confidence: 99%
“…A converging view that there may be more similarities than differences in core psychological aspects across the sexes was presented by Tomlinson-Keasey, Warren, and Elliot (1986) in their prospective investigation of suicide among gifted women. In 1970Shneidman (1971 investigated the lives of five male suicides.…”
Section: Sexmentioning
confidence: 99%